The Effect of Acupressure on Breast Milk Production in Post-Partum Mothers - Triana Indrayani; Ismi Nurani; Dewi Kurniati (Sekolah Tinggi Ilmu Kesehatan Kendal, 2022)
The coverage of exclusive breastfeeding at Puskesmas (Community Health Center) Limbangan in 2020 has only reached 61.6% so there is a gap of 23.4% from the set target of 85%. In the field, it shows that low production and ejection of breast milk in the first few days after giving birth is an obstacle in early breastfeeding. One solution to overcome non-smooth milk production is through the technique of acupressure points for lactation.This study aimed to determine the effect of acupressure on breast milk production in post-partum mothers at Puskesmas Limbangan, Garut. This study is quasi-experimental using pre-test – post-test with a control group design. The population in this study was all post-partum mothers of their first child aged 3 days amounted to 42 people who were divided into two groups, namely 21 people in the experimental group and 21 people in the control group. The samples in this study were selected using the technique of total sampling. Data analysis in this study was carried out using Paired Samples Test. The average breast milk production in the experimental group before acupressure was 119.05, and after acupressure was 213.33. Meanwhile, the average breast milk production in the control group before the intervention was 129.52, and after the intervention was 168.57. The bivariate results showed a p-value of 0.000 <0.05.